PEMENUHAN ASAS FORMIL DAN ASAS MATERIL DALAM PEMBENTUKAN UNDANG-UNDANG DI INDONESIA MENGGUNAKAN METODE OMNIBUS LAW - Ni Nyoman Asti Irawati Puja (Jurnal Ilmiah Dinamika Hukum, 2023)
The existence regulations is crucial and important in Indonesia as a legal state that adheres to the civil law ,where in this system the highest position is a constitution. Pancasila and the 1945 NRI Law are fundamental guidelines in making laws and regulations.The principle is the basic guideline that must be fulfilled so that later the legal product results, namely the laws and regulations that are produced are good, ideal, and worthy of enactment. President Joko Widodo working with the DPR as legislature-forming institution to make a law in a different way, namely by repealing and/or amending several provisions of the law at once using the omnibus law method. There is a legal issue where in forming a law one must comply with the principles of forming statutory regulations, both formal and material principles. In this research, we will discuss how to fulfill formal and material principles in the formation of laws in Indonesia using the omnibus law method?. The results of the discussion in this writing are that the fulfillment of the formal and material principles of the law adopting the omnibus law method must be based on the principles stipulated in Article 5 of Law 13 of 2022.